If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10.96 = 0.6x + 5.56 Reorder the terms: 10.96 = 5.56 + 0.6x Solving 10.96 = 5.56 + 0.6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6x' to each side of the equation. 10.96 + -0.6x = 5.56 + 0.6x + -0.6x Combine like terms: 0.6x + -0.6x = 0.0 10.96 + -0.6x = 5.56 + 0.0 10.96 + -0.6x = 5.56 Add '-10.96' to each side of the equation. 10.96 + -10.96 + -0.6x = 5.56 + -10.96 Combine like terms: 10.96 + -10.96 = 0.00 0.00 + -0.6x = 5.56 + -10.96 -0.6x = 5.56 + -10.96 Combine like terms: 5.56 + -10.96 = -5.4 -0.6x = -5.4 Divide each side by '-0.6'. x = 9 Simplifying x = 9
| 2(3x-5)-8=4(x-8)+46 | | 2x+5-4x=1 | | 3y=69 | | 2x=e^3 | | -3[x-15]=-4 | | 4x^2-28x-55=0 | | x-2(2x-1)=23 | | (4x-4xy+2y)-(2x+2xy-27y)= | | 15x+15+12x-24=180 | | sqrt(2x+1)+5=sqrt(x+12)-8 | | x-2y=23 | | 8x+22=6 | | 3.00(15.00+x)= | | -3(h-7)=5(3h+3) | | -4x+16=116 | | 2(y+6)+11=51-5y | | -2x-12=2x+10 | | 4m+16=12m+12 | | 10.00(20.00+x)=900 | | (3y-3)(y+5)= | | 4(3x-6)= | | 5+u=7 | | 15-25= | | (2x+3)(2)=25 | | 8x-3=8x-3 | | 3(2x-1)-2(3x+4)=11 | | 2x+18=8x-6 | | -1+1+(-25)= | | 0.25x-3.60= | | 15+(-22)+9= | | h=16t^2+1440t | | 3x^4-4x^3-15x^2=0 |